2004
DOI: 10.1111/j.1530-0277.2004.tb03234.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Portal Hemodynamics in Alcoholic Liver Cirrhosis

Abstract: Background: Low incidence of reversal blood flow at the portal vein has been reported by measurement in larger and extrahepatic blood vessels but not in intrahepatic blood vessels in patients with liver cirrhosis. Moreover, there is little information regarding the incidence of reversal blood on the basis of the cause of liver cirrhosis. The aim of this study was to measure the reversal blood flow in the portal vein including intrahepatic branches in patients with alcoholic and viral cirrhosis.Methods: The blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…As for vein, a prospective study showed that alcohol could increase blood pressure in the portal vein so as to inducing portal vein regurgitating and blood clots [24]. Portal venous reflux is a special feature of alcoholic cirrhosis and is rarely found in viral cirrhosis [25]. In addition, chronic alcohol ingestion activity NADPH oxidase activity to induce vascular wall damage, followed by penetration of liquid and macromolecules to trigger production of collagen, elastin, and basement membrane-like substances [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…As for vein, a prospective study showed that alcohol could increase blood pressure in the portal vein so as to inducing portal vein regurgitating and blood clots [24]. Portal venous reflux is a special feature of alcoholic cirrhosis and is rarely found in viral cirrhosis [25]. In addition, chronic alcohol ingestion activity NADPH oxidase activity to induce vascular wall damage, followed by penetration of liquid and macromolecules to trigger production of collagen, elastin, and basement membrane-like substances [26,27].…”
Section: Discussionmentioning
confidence: 99%